PENGARUH PELATIHAN, FASILITAS, DAN BUDAYA ORGANISASI TERHADAP SIKAP PERSONAL DALAM MENDUKUNG ZERO ACCIDENT PADA KARYAWAN BAGIAN PRODUKSI PT. COCA-COLA AMATIL INDONESIA CENTRAL JAVA - SEMARANG - Mulyono, Bogi -; Setyadi, Dody -; Wahyuni, Sri - (Politeknik Negeri Semarang, 2016)
This research was aimed to know theinfluence of training, facilities, and culturalorganization in support personal attitudetoward zero accident in production employessat PT. Coca-Cola Amatil Indonesia CentralJava - Semarang.The methods of data collection were interviewand questionnaire completion. The sample ofthis research were 60 respondents andanalytical method used were the validity test,reliability test, multiple linear regressionmethod, t-test, F-test, and clasic asumption..The result of regression analysis indicatedthat training, facilities, and culturalorganization had positive influence onpersonal attitude toward zero accident inproduction employees. Based on t test result,it indicated that training, facilities, andcultural organization had positive significantinfluence personal attitude toward zeroaccident in production employees. Based on Ftest, independent variables simutaneouslyinfluence the personal attitude toward zeroaccident in production employeessignificantly, with coeficient of determination(R2) of 0,532. This meant that 53,2% ofpersonal attitude toward zero accident inproduction employees could be explained byvariables of training, facilities, and culturalorganization, while remaining 46,8 % wasinfluenced by other variables which were notobserved.